STUDI POLA DISPERSI EMISI GAS SO2 DARI CEROBONG KILANG PT PERTAMINA (PERSERO) RU V BALIKPAPAN - Khairun Nisa (Sekolah Tinggi Teknologi MIGAS, 2023)
Modeling of exhaust emissions (SO2) from refinery chimneys was carried out using the Gaussian Plume model through Screen3 software. The results showed that there was an influence of wind speed and atmospheric stability on the variation in modeling results. The higher the wind speed and the more stable an atmosphere, the lower the resulting concentration value. Modeling on the worst case scenario, produces the largest possible concentration value that might occur somewhere. The distribution map of the model results is displayed following the dominant wind direction, namely to the South and North of the refinery. The difference in the magnitude of the distribution of concentration values is depicted in the color difference. The more stable the conditions of atmospheric stability, the farther the high concentration will be from the refinery. The overall value of the model results shows a concentration value that is below the quality standard value when based on PP No. 41 of 1999. Mitigation of risk management includes regular training by industry and the government regarding air emissions and ambient air at refineries; through policies to eliminate the risk of industrial accidents.